2022
DOI: 10.1186/s12891-022-05290-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical features of drop vertical jump are different among various sporting activities

Abstract: Background Risk for non-contact anterior cruciate ligament (ACL) injury can be assessed based on drop vertical jump (DVJ). However, biomechanics of DVJ may differ with various sporting activities. The purpose of the present study was to clarify whether biomechanical features of DVJ are different among various sporting activities in female athletes. Methods A total of 42 female athletes, including 25 basketball, 8 soccer and 9 volleyball players, pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Finally, the types of sports and competition levels were not unified because all participants were healthy males. A study reported that basketball players exhibit a higher knee valgus angle than soccer players [ 30 ]. Therefore, clarifying the difference in the degree of fatigue within the same sports activity is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the types of sports and competition levels were not unified because all participants were healthy males. A study reported that basketball players exhibit a higher knee valgus angle than soccer players [ 30 ]. Therefore, clarifying the difference in the degree of fatigue within the same sports activity is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this study included participants of different levels and types of previous sports activities. The level and type of sports activities may affect biomechanics during landing 51,52 . Fourth, participants were asked to keep their hands at ear level during the two landing tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This increased risk, particularly in sports that involve cutting and landing maneuvers, highlights the importance of injury prevention through identification of risky movement patterns. While knee abduction is one component of injury risk, faulty movement patterns across multiple joints directly relate to ACL injury (7)(8)(9)(10). Screenings for movement patterns associated with ACL injury mechanisms can be administered to identify athletes at risk.…”
Section: Introductionmentioning
confidence: 99%